A Synthesis of Marine Monitoring Methods With the Potential to Enhance the Status Assessment of the Baltic Sea - Mack, Leoni; Attila, Jenni; Aylagas, Eva; Beermann, Arne; Borja, Angel; Hering, Daniel; Kahlert, Maria; Leese, Florian; Lenz, Robin; Lehtiniemi, Maiju; Liess, Antonia; Lips, Urmas; et al. (Frontiers in Marine Science, 2020)
A multitude of anthropogenic pressures deteriorate the Baltic Sea, resulting in the need to protect and restore its marine ecosystem. For an efficient conservation, comprehensive monitoring and assessment of all ecosystem elements is of fundamental importance. The Baltic Marine Environment Protection Commission HELCOM coordinates conservation measures regulated by several European directives. However, this holistic assessment is hindered by gaps within the current monitoring schemes. Here, twenty-two novel methods with the potential to fill some of these gaps and improve the monitoring of the Baltic marine environment are examined. We asked key stakeholders to point out methods likely to improve current Baltic Sea monitoring. We then described these methods in a comparable way and evaluated them based on their costs and applicability potential (i.e. possibility to make them operational). Twelve methods require low to very low costs, while five require moderate and two high costs. Seventeen methods were rated with a high to very high applicability, whereas four methods had moderate and one low applicability for Baltic Sea monitoring. Methods with both low costs and a high applicability include the Manta Trawl, Encapsulated Filtration Device, Sediment Corer, Argo Float, Artificial Substrates, Citizen Observation, Earth Observation, the HydroFIA®pH system, DNA Metabarcoding and Stable Isotope Analysis.